Startling Mosaicism of the Y-Chromosome and Tandem Duplication of the SRY and DAZ Genes in Patients with Turner Syndrome - Premi, Sanjay (Public Library of Science, 2008)
Presence of the human Y-chromosome in females with Turner Syndrome (TS) enhances the risk of development of gonadoblastoma besides causing several other phenotypic abnormalities. In the present study, we have analyzed the Y chromosome in 15 clinically diagnosed Turner Syndrome (TS) patients and detected high level of mosaicisms ranging from 45,XO:46,XY = 100:0% in 4; 45,XO:46,XY:46XX = 4:94:2 in 8; and 45,XO:46,XY:46XX = 50:30:20 cells in 3 TS patients, unlike previous reports showing 5–8% cells with Y- material. Also, no ring, marker or di-centric Y was observed in any of the cases. Of the two TS patients having intact Y chromosome in >85% cells, one was exceptionally tall. Both the patients were positive for SRY, DAZ, CDY1, DBY, UTY and AZFa, b and c specific STSs. Real Time PCR and FISH demonstrated tandem duplication/multiplication of the SRY and DAZ genes. At sequence level, the SRY was normal in 8 TS patients while the remaining 7 showed either absence of this gene or known and novel mutations within and outside of the HMG box. SNV/SFV analysis showed normal four copies of the DAZ genes in these 8 patients. All the TS patients showed aplastic uterus with no ovaries and no symptom of gonadoblastoma. Present study demonstrates new types of polymorphisms indicating that no two TS patients have identical genotype-phenotype. Thus, a comprehensive analysis of more number of samples is warranted to uncover consensus on the loci affected, to be able to use them as potential diagnostic markers.